(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1862)
An account of the history of timekeeping and watchmaking in Britain and Europe. The article ends with a list of watches donated to the Society by the author, including any information he has on their makers or owners. Meeting notes for 21 May, 1860 are appended.